Relationship between carbon footprint and profits: the moderating role of clean energy innovation - Porles Ochoa, Francisco Daniel (Pontificia Universidad Católica del Perú, 2023)
Clean energy innovation is critical to the decarbonization of CO2-intensive industries that rely on fossil fuels. Nonetheless, a deeper understanding of the influence of technical innovation on firms' efforts to tackle climate change and improve economic competitiveness is needed, particularly in those industrial sectors with "hard-to-abate" CO2e emissions. This quantitative longitudinal research examines the moderating effect of clean energy innovation on the link between carbon footprint and corporate profits using a global sample of 7,827 firm-year data pertaining to 167 multinational companies between 2018 and 2021. This study uses the Bayesian method, a recommended statistical framework for fitting complex growth curve models with longitudinal data, to specify a multi-indicator latent growth curve (B-LGC) model for longitudinal moderation analysis. The findings indicate that the carbon footprint has a large positive influence on corporate profits. Furthermore, the model results support the prediction that clean energy innovation positively moderates the link between value chain (Scope 3) emissions and gross profit margin when measured using renewable energy consumption. The implications of the findings suggest that executives and managers in heavily polluting companies can achieve greater competitive advantages and transition to a net-zero emissions business by developing a comprehensive understanding of Scope 3 emissions. More significantly, policymakers should pay particular attention to these companies' Scope 3 emissions in order to develop regulation and control systems that encourage clean energy innovation.

La innovación en energías limpias es clave hacia la descarbonización de industrias intensivas en el uso de combustibles fósiles. No obstante, existe la necesidad de una mayor comprensión del impacto de la innovación tecnológica en los esfuerzos de las empresas por combatir el cambio climático y mejorar su competitividad, principalmente en aquellos industrias “difíciles de reducir” las emisiones de CO₂e. Usando una muestra global de 7 827 observaciones de empresa-año correspondientes a 167 empresas internacionales entre el 2018 y 2021, esta investigación longitudinal cuantitativa examina el efecto moderador de la innovación en energías limpias en el vínculo entre la huella de carbono y la rentabilidad corporativa. Para este análisis de moderación longitudinal, se emplea el método bayesiano, un marco estadístico recomendado para ajustar modelos de curva de crecimiento complejos con datos longitudinales, estimando para ello un modelo de curva de crecimiento latente (B-LGC) de múltiples indicadores. Los resultados revelan un impacto significativo de la huella de carbono sobre las ganancias. Asimismo, los resultados respaldan la hipótesis de que la innovación en energías limpias, cuando es medida usando el consumo de energías renovables, modera positivamente la relación entre las emisiones de la cadena de valor (Alcance 3) y el margen de utilidad bruta. Estos hallazgos implican que una comprensión más detallada de las emisiones de toda la cadena de valor (Alcance 3) por parte de los ejecutivos y gerentes de las empresas, representa un mecanismo efectivo para obtener mayores ventajas competitivas, y al mismo tiempo llegar a ser un negocio con cero emisiones netas. Mas importante aún, los formuladores de políticas deberían prestar especial atención a las emisiones de Alcance 3, para formular mecanismos regulatorios y de control que estimulen la innovación en energías limpias.
Keywords: Innovaciones tecnológicas; Control ambiental; Desarrollo sostenible--Empresas; https://purl.org/pe-repo/ocde/ford#5.02.04